Lepton flavor violating processes in the minimal 3-3-1 model with sterile neutrinos. (27th September 2019) - Machado, A C B; Montaño, J; Pleitez, V
Abstract: We consider the minimal 3-3-1 model adding three right-handed neutrinos that transform as singlet under the SU (3) L  ⨂  U (1) X symmetry. This model predicts flavor violating interactions in both quark and lepton sectors, since all the charged fermions mass matrices cannot be assumed diagonal in any case. Here we accommodate the lepton masses and the Pontecorvo–Maki–Nakagawa–Sakata matrix at the same time, and as a consequence the Yukawa couplings and the unitary matrices which diagonalize the mass matrices are no longer parameters. We study some phenomenological consequences, i.e., l i → l j l k l ̄ k and l i  →  l j γ which are induced by the neutral and doubly charged particles present in the model. In particular we show that if μ → ee e ̄ is observed in the future, the only particle in the model that could explain this decay is the doubly charged vector bilepton mediator, because the contribution due to the doubly charged and neutral scalars is suppressed.